Disordered bone metabolism in hereditary spherocytosis patients. Issue 1 (1st January 2019) - Cesur, Mahmut; Temiz, Fatih; Acıpayam, Can; Kılınc, Metin; Seringec Akkececi, Nurten
ABSTRACT: Aim: This study was planned to evaluate bone health in patients with hereditary spherocytosis. Materials and methods: In this prospective study, a total of 30 hereditary spherocytosis patients which followed in the Pediatric Hematology and Oncology Department of KSU Medical Faculty and 30 patients for control group were included. Patient and control group were chosen equal in age and sex. Hemogram and biochemical tests (serum calcium, phosphorus, alkaline phosphatase, parathormone, vitamin D) and osteocalcin were studied from the patient and control groups. Also DXA examination was performed in the patient group. Results: There was a significant difference in hemogram parameters between the two groups due to hemolytic anemia in hereditary spherocytosis patients. In the patient group, osteocalcin was 6.88 ± 4.35 ng/ml, vitamin D was 17.74 ± 7.76 ng/ml and in the control group osteocalcin was 11.93 ± 8.92 ng/ml, vitamin D was 24.04 ± 11.70 ng/ml. There was a statistically significant difference between the vitamin D and osteocalcin levels of the two groups ( p  = 0.017 and 0.008, respectively). Bone density was assessed in the patient group. In patients DXA results showed lower Z-scores then the normal population according to age and sex. Conclusion: Hereditary spherocytosis patients should be followed closely in terms of development, puberty, bone health as they are in other hemolytic anemias. Nutritional recommendations, vitamin D supplementation, physical activity should be advised to protect bone health.